Milk as a symbol of immortality in the “Orphic” gold tablets from Thurii and Pelinna - Torjussen, Stian Sundell (Nordlit, 2014)
This article offers an interpretation of the enigmatic “kid-in-milk” formula which appears in four of the “Orphic” gold tablets from Thurii and Pelinna. These tiny tablets accompanied the dead in their graves and contained texts of various lengths which were believed to help the deceased on his or her journey to the otherworld. Many see the tablets as Orphic texts, but this question has been highly debated during the last century. The four tablets in question, from two sites in southern Italy and Greece, tell how the deceased has suffered in life, but that he or she has attained immortality through initiation. The immortalization was referred to and summed up in the “kid-in-milk” formula, where, it is argued, milk was a direct reference to immortality. Thus milk in this eschatological context is a symbol of immortality which served as a focal point for both the text and the initates.